Emergency remote learning during the COVID-19 pandemic: Perspectives of elementary schools in rural area of Indonesia - Hermanto Hermanto; Zulela Ms.; Muhammad Japar (UIN Raden Mas Said Surakarta, 2022)
Amidst the COVID-19 pademic, the Indonesian government issued a distance and online learning policy so that students study in a state of emergency. Education is a conscious effort to provide a meaningful learning experience for students. This experience includes cognitive, affective, and psychomotor aspects. This research is at the cutting edge of portraying the emergency remote learning of elementary schools in rural area of Indonesia in response to the COVID-19 pandemic. In the COVID-19 emergency, the Indonesian government issues a distance and online learning policy so that students can study even in a state of social distancing. The digital transformation of teachers and students is the impact of the learning process during the pandemic since the beginning of 2020. This research was a qualitative research employing a case study. Sources of data were teachers and students in elementary schools selected by purposive sampling. The technique applied interview and observation using interview sheet instruments and field notes about the reality of the implementation of education in schools. The results indicate that 80.81% of the learning process for low grade students is fully controlled by their parents, while in high grade students online and distance learning processes are not as formal as they should be. The implications of the results of this study illustrate that basic education in Indonesia has not yet ready in terms of human resources and technology, especially in the rural areas of frontier, outermost and underdeveloped. The contribution in this research is to provide an understanding to education observers how the process or learning experience is in pandemic and normal situations.